2016
DOI: 10.1016/j.jmau.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dendritic cell immune functions by plant components

Abstract: Dendritic cells (DCs) are the key linkage between innate and adoptive immune response. DCs are classified as specialized antigen-presenting cells that initiate T-cell immune responses during infection and hypersensitivity, and maintain immune tolerance to self-antigens. Initiating T-cell immune responses may be beneficial in infectious diseases or cancer management, while, immunosuppressant or tolerogenic responses could be useful in controlling autoimmunity, allergy or inflammatory diseases. Several types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…In this study, DCs were successfully generated from cryo CB in culture medium containing GM-CFS, IL-4, and TNF-α, which consistently showed a DC marker expression profile, such as CD80high, CD86high, CD40high, HLA-DRhigh, CD123low CD56low, and CD14low. Cryo CBMDCs expressed a typical DC morphology with thin and long dendrites, which have been described in previous reports [21,22,[26][27][28][29][30]. Thus, our results indicate that cryo CB can be a potential source for DC generation, which then may be developed into immunotherapies.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, DCs were successfully generated from cryo CB in culture medium containing GM-CFS, IL-4, and TNF-α, which consistently showed a DC marker expression profile, such as CD80high, CD86high, CD40high, HLA-DRhigh, CD123low CD56low, and CD14low. Cryo CBMDCs expressed a typical DC morphology with thin and long dendrites, which have been described in previous reports [21,22,[26][27][28][29][30]. Thus, our results indicate that cryo CB can be a potential source for DC generation, which then may be developed into immunotherapies.…”
Section: Discussionsupporting
confidence: 85%
“…2,25 According to several studies, Biophytum petersianum Klotzsch is able to induce especially the activation of dendritic cells and also the response to T cells, B cells, and NK cells related to the role of saponin content in inducing the production of cytokines, interleukins, and interferons. 15,26 The effect of Biophytum on apoptosis as an anti-tumor based on the previous research was gotten by regulating Bcl-2, Caspase-3 and p-53 genes and the production of inflammatory cytokines and tumor activated macrophage. 25,27 Saponin extract of in vitro studies used human endometrial stromal cells from post-surgical patients with a diagnosis of endometriosis and it was known to able to induce apoptosis in endometrial cells through the modulation of miR-21-5p.…”
Section: Discussionmentioning
confidence: 99%
“…The immune‐modulating effects of astragalus root and elderberry fruit extracts were examined in bone marrow‐derived murine DCs. The ELISA and RT‐PCR tests indicated that both extracts enhanced IFN‐ß production, increased endocytosis in immature DCs, upregulated toll‐like receptor 3, and enhanced the IL‐12, IL‐6, IL‐1b, and TNFα cytokines release (Aldahlawi, 2016 ). Also, induction, maturation, and differentiation of DCs were reported by Mucuna pruriens extract (Kurokawa et al, 2011 ).…”
Section: Plants and Immunostimulationmentioning
confidence: 99%
“…Also, induction, maturation, and differentiation of DCs were reported by Mucuna pruriens extract (Kurokawa et al, 2011 ). The Abelmoschus esculentus increased the expression of IL‐12, interferon IFNγ, and stimulated DCs by modulating the expression of class II‐MHC and costimulatory CD + 80/86 molecules (Aldahlawi, 2016 ; Sheu & Lai, 2012 ).…”
Section: Plants and Immunostimulationmentioning
confidence: 99%